Ferrocenes : ligands, materials and biomolecules - Štěpnička, Petr (J. Wiley, 2008)
Provides the reader with a background overview and describes recent advances in the development and application of ferrocene compounds, including: synthesis and catalytic utilisation of chiral and non-chiral ferrocene ligands, ferrocene-based sensors, electrooptical materials, ferrocene polymers, liquid-crystalline materials, crystal engineering with ferrocene compounds, and the bioorganometallic chemistry of ferrocene.